The clue of the leaning chimney - Keene, Carolyn (New York : Grosset & Dunlap, 1995)
A rare Chinese vase is stolen from a pottery shop. Nancy and the owner of the shop feel that locating "the leaning chimney" will provide the clue to the vase and other stolen articles.
Keywords: Detective and mystery stories; Drew, Nancy -- (Fictitious character) -- Fiction; Adventure stories; Mystery and detective stories; Mystery fiction